IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF DENGAN PERMAINAN LOKAL DALAM PENGUATAN KARAKTER PADA MATA PELAJARAN PPKn - Yasmin, Regita; Rejeki, Sri; Winata, Aliahardi (Jurnal Muara Pendidikan, 2024)
This study aims to determine the impact of local games (X) on students' character development (Y). A quantitative research method was employed, collecting data via questionnaires with 15 items for the local games variable (X) and 15 for the character assessment variable (Y). The research procedure included instrument preparation, instructional process, data analysis, interpretation, and conclusion formulation. The findings indicate that local games influence students' character development, with an average score of 85.69. The F-statistic value of 0.06 and significance level of 0.941 suggests that while local games impact character development, not all character aspects are significantly affected. The character trait of "curiosity" had the highest influence, with a 92.00% rating, highlighting a strong positive impact of local games on this trait. Conversely, the "hard work" trait showed the lowest influence, with a score of 80.67%, indicating that local games have a limited impact on this character trait. Traits such as cooperation, independence, honesty, tolerance, friendliness and communicativeness, responsibility, and creativity displayed scores above the average of 85.69%. However, independence and hard work were below the minimum threshold of 80.67%. These results suggest that while local games positively influence some aspects of character, they do not significantly change all character traits. It is recommended that local games be utilized primarily for fostering group-oriented character traits.